State‐of‐Charge: Monitoring the State‐of‐Charge of a Vanadium Redox Flow Battery with the Acoustic Attenuation Coefficient: An In Operando Noninvasive Method (Small Methods 12/2019). Issue 12 (2nd December 2019) - Zang, Xiaoqin; Yan, Litao; Yang, Yang; Pan, Huilin; Nie, Zimin; Jung, Ki Won; Deng, Zhiqun Daniel; Wang, Wei
Abstract : In article number 1900494 by Zhiqun Daniel Deng, Wei Wang, and co‐workers, an ultrasonic probing approach that can measure the acoustic properties of a vanadium redox flow battery electrolyte is designed to monitor the state‐of‐charge (SOC) of flow batteries online noninvasively. The SOC estimated from the acoustic attenuation coefficient is found to be robust to temperature variation.